A Nuclei-Based Conceptual Model of (Eco)evolutionary Dynamics in Fungal Heterokaryons - Lakovic, Milica; Rillig, Matthias C. (Frontiers in Microbiology, 2022)
Filamentous fungi are characterised by specific features, such as multinuclearity, coexistence of genetically different nuclei and nuclear movement across the mycelial network. These attributes make them an interesting, yet rather underappreciated, system for studying (eco)evolutionary dynamics. This is especially noticeable among theoretical studies, where rather few consider nuclei and their role in (eco)evolutionary dynamics. To encourage such theoretical approaches, we here provide an overview of existing research on nuclear genotype heterogeneity and its sources, such as mutations and vegetative non-self-fusion. We then discuss the resulting intra-mycelial nuclear dynamics and the potential consequences for fitness and adaptation. Finally, we formulate a nuclei-based conceptual framework, which considers three levels of selection: a single nucleus, a subpopulation of nuclei and the mycelium. We compare this framework to other concepts, for example those that consider only the mycelium as the level of selection, and outline the benefits of our approach for studying (eco)evolutionary dynamics. Our concept should serve as a baseline for modelling approaches, such as individual-based simulations, which will contribute greatly to our understanding of multilevel selection and (eco)evolutionary dynamics in filamentous fungi.